COVID-19 AND LONG-DISTANCE COACH SERVICES IN EUROPE: THE IMPACT OF CHANGING PASSENGER BEHAVIOR - Michał TARACHA; Laurent GUIHÉRY (Transport Problems)
The aim of this study is to present the consequences of the COVID-19 crisis in the long-distance coach market in Europe. Firstly, the literature review depicts the dynamic situation of European long-distance transport service providers. It is reiterated that the disruptions to long-distance coach transport triggered by the COVID-19 pandemic are multidimensional. Secondly, 10 econometric panel models, including one spatial and two dynamic panel models, were constructed for 505 or 495 regions (depending on the model) of 26 European countries. The analysis allowed us to draw conclusions about the impact of excess mortality, public sentiment, population density, and infrastructure quality on the number of long-distance FlixBus coach departures. Models indicate that increased anxiety associated with COVID-19 leads to a drop in the number of departures even when mortality anomaly is accounted for. Moreover, the number of departures changed more significantly in response to an increased infection rate in 2021 compared to 2020. This may indicate that long-distance coach companies were encouraged to implement new policies aiming at a lower frequency of trips, thereby increasing certainty that planned departures would not be canceled at the last minute. This can serve as an evidence of a shift in companies’ focus towards greater flexibility of their offers.